The pathway for perception and transduction of low-temperature signals in Synechocystis - Suzuki, Iwane (Oxford University Press, 2000)
Low temperature is an important environmental factor that has effects on all living organisms. Various low-temperature-inducible genes encode products that are essential for acclimation to low temperature, but low-temperature sensors and signal transducers have not been identified. However, systematic disruption of putative genes for histidine kinases and random mutagenesis of almost all the genes in the genome of the cyanobacterium Synechocystis sp. PCC 6803 have allowed us to identify two histidine kinases and a response regulator as components of the pathway for perception and transduction of low-temperature signals. Inactivation, by targeted mutagenesis, of the gene for each of the two histidine kinases and inactivation of the gene for the response regulator depressed the transcription of several lowtemperature-inducible genes.